ANALISIS KORELASI ANTARA KANDUNGAN SENYAWA BIOAKTIF DENGAN AKTIVITAS ANTIOKSIDAN PADA EKSTRAK DAUN BAMBU DURI (Bambusa blumeana) - Ni Made Sri Wahyuni; Luh Putu Wrasiati; Amna Hartiati (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Bambu duri leaves are natural ingredients that has the potential as a source of antioxidants. Bioactive compounds that can be used as a source of antioxidants can be maximally obtained through controlling the extraction process. This study aims to: (i) determine the effect of temperature and maceration time on the content of bioactive compounds (total phenolic and total flavonoids) and antioxidant activity (IC50) of bambu duri leaf extract, (ii) determine the correlation value between bioactive compounds and antioxidant activity. This study was designed using two factors. The first factor is the maceration temperature consisting of 30, 45, and 60°C. The second factor is the maceration time consisting of 24, 36, and 48 hours. From these two factors, 9 treatment combinations were obtained and analyzed twice. Correlation values were analyzed using Pearson correlation analysis and multiple correlation analysis. The results showed that the interaction between temperature and maceration time had an effect on the content of bioactive compounds (total phenolic, total flavonoids) and the antioxidant activity of the bambu duri leaf extract. The results of Pearson correlation analysis showed that flavonoid compounds had the highest correlation value with antioxidant activity. The results of multiple correlation analysis between bioactive compounds (total phenolic and total flavonoids) with the antioxidant activity of bambu duri leaf extract resulted in a correlation coefficient (r=0.983) which was included in the very strong relationship category, the regression equation Y=1445-2.941X1-4.940X2, and the coefficient of determination R2= 0.967. The determination value indicates that 96.7% of antioxidant activity is influenced by the content of bioactive compounds in the form of phenolic and flavonoids, while the remaining 3.3% is influenced by other factors.